Collaborative Governance of the Stunting Reduction Program in Majene District - ., Wirdaningsih; Palutturi, Sukri; ., Indar; Razak, Amran; ., Ridwan; Syam, Aminuddin; Mallongi, Anwar (Journal of Cultural Analysis and Social Change, 2026)
Wirdaningsih. Collaborative Governance in Stunting Mitigation in Majene Regency (supervised by Sukri Palutturi and Indar). Background. The problem of stunting in toddlers in Indonesia, particularly in Majene Regency, West Sulawesi, remains a problematic issue whose prevalence continues to be addressed. Government agencies have implemented multiple initiatives to reduce stunting, yet stunting prevalence in Majene Regency, West Sulawesi, has not declined. Aim. This study aims to analyze the implementation of collaborative governance in stunting mitigation in Majene Regency. Method. Qualitative methods were applied, with data gathered through interviews. Key and supporting informants were selected using purposive sampling. Result. The collaborative governance process, from the dimension of mobilizing shared principles, has fulfilled the collaboration component in implementing stunting mitigation in Majene Regency. Shared motivation has fulfilled the collaboration component in implementing stunting mitigation in Majene Regency. Capacity for Joint Action has fulfilled the collaboration component in implementing stunting mitigation in Majene Regency. Collaborative actions were implemented effectively by Pentahelix actors Stakeholder involvement remained incomplete, although collaboration contributed substantially to lowering stunting cases. Local government is therefore expected to take a more proactive role in implementing stunting reduction efforts in Majene Regency. Conclusion. One improvement that can be made is that the local government needs to strengthen cross-sectoral collaboration forums in stunting management.